Association between plasma trimethylamine N-oxide and coronary heart disease: new insights on sex and age differences - Sun, Yangyang; Lin, Xipeng; Liu, Zhihao; Hu, Lihua; Sun, Pengfei; Shen, Geng; Fan, Fangfang; Zhang, Yan; Li, Jianping (Frontiers in Cardiovascular Medicine, 2024)
Aim: Elevated plasma Trimethylamine N-oxide (TMAO) is related to atherosclerosis. Whether the relationship of TMAO and coronary heart disease (CHD) is influenced by sex or age is uncertain. We aim to explore the sex and age differences in the relationship between plasma TMAO and CHD risk and severity.A case-control study was conducted in patients undergoing elective coronary angiography. Matched by sex, age (± 2 years) and operation date (± 180 days), a total of 429 CHD case-control pairs were included. Plasma TMAO was quantified using liquid chromatography-tandem mass spectrometry. Logistic regression analyses were performed to evaluate the association between plasma TMAO and CHD risk and severity.The overall median (interquartile range) plasma TMAO level was 0.11 (0.06 -0.18) μg/mL. After stratification by sex and age, and adjustment for common CHD risk factors, the association between TMAO and CHD risk was significant in the older (≥ 65 years) male subgroup (OR = 1.57, 95% CI: 1.09 -2.28, P = 0.016), but not in other sex-age subgroups (all P > 0.05). The relationship of plasma TMAO and CHD risk was modified by age (adjusted P interaction = 0.001) in male individuals. Plasma TMAO was also associated with a higher risk of multi-vessel disease (MVD) in male CHD patients (OR = 1.65, 95% CI: 1.18 -2.32, P = 0.004), but not in females.Conclusions: Plasma TMAO is significantly positively associated with the risk and severity of CHD in Chinese men. Age has an interactive effect on the relationship between plasma TMAO and CHD risk in men. Our findings warrant further investigation.